Stepping Stones for the Unemployed : The Effect of Temporary Jobs on the Duration until Regular Work - Marloes Zijl; Gerard J. van den Berg; Arjan Heyma (Institute for the Study of Labor (IZA), 2004)
Individual labour market transitions from unemployment into temporary work are often succeeded by a transition from temporary into regular work. We investigate whether temporary work increases the transition rate to regular work. In that case, temporary work may enhance labour market efficiency. We use longitudinal survey data of individuals to estimate a multi-state duration model, applying the ?timing of events? approach. To deal with selectivity, the model incorporates transitions from unemployment to temporary jobs and unobserved determinants of the transition rates. The data contain multiple spells in labour market states at the individual level. We analyse the results using novel graphical representations. The results unambiguously show that temporary jobs serve as stepping stones towards regular employment. They shorten the duration of unemployment and they substantially increase the fraction of unemployed workers who have regular work within a few years after entry into unemployment, as compared to a situation without temporary jobs.
Keywords: J64; C41; 330; unemployment; fixed term contracts; temporary work; job search; duration model; treatment effect; Befristeter Arbeitsvertrag; Berufliche Integration; Arbeitsuche; Arbeitslosigkeit; Dauer; Schätzung; Niederlande